The multiple functions and benefits of small farm agriculture in the context of global trade negotiations - Rosset, Peter (2000)
Peter Rosset challenges the conventional wisdom that small farms are backward and unproductive. Using evidence from southern and northern countries he demonstrates that small farms are `multi-functional' - more productive, more efficient, and able to contribute more to economic development than large farms. He analyses the threats posed to small farmers by today's trade liberalization and concludes with a call to unite against an Agreement on Agriculture that might make their continued existence impossible. - Reproduced
Keywords: Social justice; Liberalization; Food supply; Environment; Biodiversity; Agriculture